Efektifitas Perda Kabupaten Klungkung No 2 Tahun 2010 dalam Upaya Pelestarian Lingkungan di Pantai Watu Klotok - Ketut Danu Yudistira; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
The environmental condition in Klungkung Regency has shown some signs of increasing environmental damage and pollution every year. To maintain and preserve the environment by the surrounding community, the Klungkung Regency Government issued Regional Regulation Number 2 of 2010 concerning Control of Environmental Damage and Pollution. The purposes of this study are to examine the effectiveness of Perda No. 2 of 2010 and to examine the obstacles in enforcing Perda No. 2 of 2010. This study was designed with empirical legal research with a statutory and conceptual approach. Data were collected through field interview techniques. The data used are primary and secondary data. After the research data was collected, the researchers then analyzed using descriptive qualitative methods. The results showed that the effectiveness of the Regional Regulation in an effort to stop the level of pollution on the Watu Klotok beach with preventive and repressive efforts through. Administrative sanctions in the form of verbal warnings, written warnings, criminal sanctions or civil fines for environmental damage or pollution. The obstacles in implementing this regional regulation are law enforcement officers, community culture, economy and public awareness. So that the effectiveness of the regulation has not been implemented effectively by law enforcers in terms of imposing sanctions. Therefore, the Klungkung Regency Government must be more firm and wise in implementing the existing legal regulations.